Sorte versus habilidade na análise de desempenho de fundos de investimentos em ações no Brasil - Silva, Wandermon Corrêa (2012)
This dissertation aims to contribute to the mainstream in Asset Pricing Theory, to analyze the performance of stock mutual funds in Brazil, for a panel with 75 mutual funds type ANBIMA Active Ibovespa which have survived during the period between Jan-1998 and Dec-2008, identifying those whose result is simply due to good luck or bad luck and those whose result is due to the skill or lack of skill of their managers. Following the methodology developed in Fama and French (1992, 1993), we built two factors, mutual funds zero cost equal weighted portfolios, able to accommodate the size and performance effects observed for these assets, which are used in some applications in an extended version of Capital Asset Pricing Model (CAPM). Both effects, which seem to play a relevant role due to the inefficiency of the CAPM model to price big funds with huge relative performance (very high or very low), are partially accommodated when one adds factors, which are significant jointly in 50% of the 75 funds analyzed. The main evidences obtained running individual time series regressions are corroborated if one uses the panel technique estimation with random effects, where both factors seem to be vital if one intends to better understand the returns of the mutual funds in Brazil. To analyze the performance of the funds, the methodology developed in Fama and French (2010) was used, in which, by bootstrap techniques, the cross-section of the performance of investment funds are modeled. For most of the funds that had significant outperformance, based on the estimated alphas in individual regressions, performance due to chance was identified. In the factors model proposed, only three funds really outperformed due to the ability of their managers, all those linked to private financial institutions. The factor model proved to be more accurate in characterizing the randomness of performance with the appropriate criteria.